Seasonal hydrogen storage for residential on- and off-grid solar photovoltaics prosumer applications: Revolutionary solution or niche market for the energy transition until 2050?. (15th June 2023) - Keiner, Dominik; Thoma, Christian; Bogdanov, Dmitrii; Breyer, Christian
Highlights: Strong seasonality lowers self-consumption ratio in PV prosumer systems. Heat demand and electric vehicles require micro on-site sector coupling. Seasonal hydrogen storage offers only limited solution for bottlenecks. Globally, PV and battery systems offer best cost advantage for majority of regions. Seasonal storage only required in Nordic countries for off-grid operation. Abstract: Appropriate climate change mitigation requires solutions for all actors of the energy system. The residential sector is a major part of the energy system and solutions for the implementation of a seasonal hydrogen storage system in residential houses has been increasingly discussed. A global analysis of prosumer systems including seasonal hydrogen storage with water electrolyser, hydrogen compressor, storage tank, and a fuel cell studying the role of such a seasonal household storage in the upcoming decades is not available. This study aims to close this research gap via the improved LUT-PROSUME model, which models a fully micro sector coupled residential photovoltaic prosumer system with linear optimisation for 145 regions globally. The modelling of the cost development of hydrogen storage components allows for the simulation of a residential system from 2020 until 2050 in 5-year steps in hourly resolution. The systems are cost-optimised for either on– or off-grid operation in eight scenarios including battery electric vehicles, which can act as an additional vehicle-to-home electricity storage for the system. Results show that implementation of seasonal hydrogen systems only occurs in least cost solutions in high latitude countries when the system is forced to run in off-grid mode. In general, a solar photovoltaic plus battery system including technologies that can cover the heat demand is the most economic choice and can even achieve lower cost than a full grid supply in off-grid operation for most regions until 2050. Additional parameters including the self-consumption ratio, the demand cover ratio, and the heat cover ratio can therefore not be improved by seasonal storage systems if economics is the main deciding factor for a respective system. Further research opportunities and possible limitations of the system are then identified.